Machine learning and big data : concepts, algorithms, tools and applications - Dulhare, Uma N.; Ahmad, Khaleel; Khairol Amali Bin Ahmad (Wiley-Scrivener, 2020)
"Machine learning with big data technologies create new opportunities to understand the various data process related to medical or environmental aspects of agriculture. Machine learning as a field is now incredibly pervasive, with applications spanning from business intelligence to homeland security from analyzing biochemical interactions to structural monitoring of aging bridges, and from emissions to astrophysics, etc. As we are entering the Industrial Revolution 4.0, BD/ML applications, in combination with IoT/Cloud technologies, are fundamentally changing any domain-specific industry. Development of this field is very important because it can help to enhance human life by the automation system, which in turn has far-reaching effects for economic, psychological, educational and organizational improvements to the way we work, teach, learn and care for ourselves and each other"--